Analysing Waiting Times and Service Utilization Using Simulation: A Study of Kluang Rail Coffee - Tan, Ee Qi; Atan, Siti Anisah (Research in Management of Technology and Business, 2025)
The food service industry in Malaysia is witnessing continuous growth, driven by the increasing prosperity and sophistication of its customers. The full- service restaurants which offer table service and a wide variety of food and beverage options, are vital to this industry. However, many Malaysian restaurants struggle with customer retention, which is typically caused by service concerns, particularly long waiting times. One of the establishments that is facing this challenge is Kluang Rail Coffee, located in Pusat Perniagaan Tasik, as customers have shared their prolonged waiting times at the restaurant. Therefore, the purpose of this study is: (1) to determine the total customer exits, service process utilisation, and average time in the system to evaluate the waiting times in the restaurant, and (2) To propose practical recommendations for reducing waiting time and enhancing customer satisfaction at Kluang Rail Coffee. Drawing on previous research on waiting time and simulation in the food and beverage business, this study uses time study and simulation methodologies to model and simulate scenarios, finding solutions for reducing waiting times. The data sample of 30 customers from each service step will be observed to collect primary data. The simulation procedure consists of identifying objectives, gathering and analysing system data, constructing and validating the model, conducting simulation experiments, and presenting results with recommendations for improvement. Finally, this study aims to understand and minimise variables that contribute to high wait times at Kluang Rail Coffee, thereby increasing customer satisfaction and operational efficiency.